Ucapan Syukur dalam Penyembahan Kemuliaan TUHAN: Kajian Berdasarkan 2 Tawarikh 7:1-3 - Julius Manahara Hutabarat; Yobel El Dasso Lumban Gaol (Jurnal Pendidikan Agama dan Teologi, 2024)
Giving thanks is our way of acknowledging and thanking God for His promise that despite our hardships and sufferings He will never leave us. From 2 Chronicles 7:1-3 we can learn from Solomon where after finishing his prayer God responded by sending fire from heaven which was a sign of God's response to his prayer. Fire shows the glory of God that fills the temple outside and inside the temple and thanksgiving requires humility when offering burnt offerings and communion offerings where God also warns to build an altar which is a reminder of God's mercy and forgiveness to man. God wants us to be a house of prayer, Christians who are called houses of prayer are Christians who like to pray, praise and worship God people who have a close relationship with God at all times, having a close relationship with God means not only talking to God, but we must also be able to hear God's voice.